Characteristics of the Floating Hip in Patients with Polytrauma - Tanasiienko, P.V.; Huriev, S.O.; Kovalyshyn, I.V. (TERRA ORTHOPAEDICA, 2025)
Introduction. The term “floating hip” refers to a group of injuries characterized by ipsilateral fractures of the bones on both sides of the joint, which are thus devoid of skeletal communication.Objective. The objective of our work was to determine the clinical and nosological characteristics of patients with a floating hip and polytrauma and its impact on the choice of treatment for this category of patients.Material and Methods. The study analyzed the treatment of 77 patients with ipsilateral hip fractures resulting from polytrauma. The patients were treated in the Polytrauma Department of the Kyiv City Clinical Emergency Hospital in the period from 2014 to 2023 and met the selection criteria for our study.Results. Among the patients of our study, 55 (71.4%) were males and 22 (28.6%) were females. In 100.0% of cases, the cause of the floating hip was severe high-energy trauma. Among the study group, 46 (59.7%) cases were caused by road accidents, 27 (35.1%) by falls from a height, and 4 (5.2%) by criminal injuries. A direct blow was the mechanism of injury in 100.0% of cases. Among patients with polytrauma, the most common fractures were simple fractures of the acetabulum of type C (47.4%) and type B (36.8%), as well as fractures of the anterior wall of type B (60.0%) and the posterior wall of type B (53.8%) and type C (38.5%). The analysis of hip fractures in patients with a floating hip and polytrauma indicated that the diaphyseal part of the femur was damaged most often, which was found in 53.2% of the study sample, with type B fractures prevailing (58.5%). Injuries to the proximal part of the thigh were detected in 40.3% of patients, with type A being the most common (41.9%).Conclusions. The analysis of the clinical and nosological characteristics of the floating hip in polytrauma patients indicates the need to develop and implement a new, more adapted classification of such injuries in patients with polytrauma.